Effects of chronic and subtoxic chlorobenzenes on adrenocorticotrophic hormone release - Molnár Zsolt (JOURNAL OF ENVIRONMENTAL SCIENCES, 2015)
Many environmental chemicals and pesticides have been found to alter neuroendocrine communication in exposed biological objects. The environmental loads have primary and secondary effects that can alter the homeostatic regulation potential. Since it is difficult to avoid human exposition, a potentially important area of research to develop in vivo and in vitro experimental models. In this context, the primary aim of this study was to demonstrate the effects of chlorobenzenes on adrenocorticotrophic hormone (ACTH) release. In our experimental study, male Wistar rats were exposed to 0.1, 1.0 and 10mug/b.w. (body weight)kg of 1,2,4- trichlorobenzene and hexachlorobenzene (ClB) mix via gastric tube for 30, 60 or 90days. At the endpoints of the experiment blood samples were taken and animals were decapitated. Primary, monolayer adenohypophysis cell cultures were prepared by enzymatic and mechanical digestion. The ACTH hormone content in serum and supernatant media was measured by immuno-chemiluminescence assay. The Mg(2+)-dependent ATPase activity was determined by modified method of Martin and Dotty. Significant differences were detected in the hormone release between the control and treated groups. The hormone release was enhanced characteristically in exposed groups depending upon the dose and duration of exposure. The Mg(2+)-ATPase activity enhanced after chronic and subtoxic ClB exposition. Light microscopy revealed that the adenohypophysis seemed to be more abundant. Results indicate that Wistar rats exposed to subtoxic ClB have direct and indirect effects on hypothalamus-hypophysis-adrenal axis.